The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/aas.13225
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tissue oxygen tension, venous saturation, and Fick‐based assessments of cardiac output during hyperoxia

Abstract: SvO acutely changes following changes in PaO even absent changes in measured DO . This may lead to errors in Fick estimates of CI. Further work is necessary to understand the impact of this phenomenon in disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
2
8
3
Order By: Relevance
“…In a similar study on swine, Perry et al evaluated the accuracy of Fick-CO assessments with an increase in FIO2, [30] while their conclusions contradict our findings. Further analysis of their data revealed that the SvO2 values were much lower in swine (58.2…”
Section: Increased Fio 2 Vs Fick-cocontrasting
confidence: 93%
See 2 more Smart Citations
“…In a similar study on swine, Perry et al evaluated the accuracy of Fick-CO assessments with an increase in FIO2, [30] while their conclusions contradict our findings. Further analysis of their data revealed that the SvO2 values were much lower in swine (58.2…”
Section: Increased Fio 2 Vs Fick-cocontrasting
confidence: 93%
“…In a similar study on swine, Perry et al evaluated the accuracy of Fick-CO assessments with an increase in FIO2, [30] while their conclusions contradict our findings. Further analysis of their data revealed that the SvO2 values were much lower in swine (58.2 ±7.27% under FIO2 = 0.6, and 61.0 ±6.7% under FIO2 = 0.8) than in the humans in the current study (79.9 ±6.4% under FIO2 = 0.56, and 85.1 ±5.6% under FIO2 = 0.92).…”
Section: Increased Fio 2 Vs Fick-cocontrasting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis, however, is not supported by animal and human experiments. In pigs subjected to increasing FiO 2 , both cerebral and myocardial tissue oxygen tension (PtO 2 ) increased proportionally with increasing FiO 2 [53,54]. When pigs were subjected to haemodilution until their electrocardiogram showed ischaemic changes, hyperoxia, although it caused coronary vasoconstriction and reduced coronary blood flow, preserved myocardial oxygenation and improved electrocardiogram abnormalities [55].…”
Section: Vasoconstriction and Cellular Oxygen Deliverymentioning
confidence: 99%
“…Nitrite reduced heart rate in hypoxia in both experiments without impacting V O2, this means that according to the Fick equation, either stroke volume must increase to maintain cardiac output, or oxygen delivery to the systemic tissue must become more efficient to maintain V O2 (50). The mechanism cannot be determined by our current data set.…”
Section: Discussionmentioning
confidence: 69%